2017
DOI: 10.1126/sciadv.1602783
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystalline germanium nanomembrane photodetectors on foreign nanocavities

Abstract: High-yield, high throughput method creates nanomembrane photodetectors with unique optoelectronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…In particular, this mechanism has been employed to enhance the optical absorption of planar ultrathin photocatalytic α‐Fe 2 O 3 films for efficient water splitting . By controlling the planar cavity structure, we demonstrated that the optical absorption within 1.5‐nm‐thick Ge film and MoS 2 monolayers can be enhanced significantly, opening the door to high‐efficiency ultrathin‐film energy conversion materials, structures, and devices . Importantly, this principle is general and can be implemented into photocatalytic systems to boost the photoconversion efficiency.…”
Section: Introductionmentioning
confidence: 94%
“…In particular, this mechanism has been employed to enhance the optical absorption of planar ultrathin photocatalytic α‐Fe 2 O 3 films for efficient water splitting . By controlling the planar cavity structure, we demonstrated that the optical absorption within 1.5‐nm‐thick Ge film and MoS 2 monolayers can be enhanced significantly, opening the door to high‐efficiency ultrathin‐film energy conversion materials, structures, and devices . Importantly, this principle is general and can be implemented into photocatalytic systems to boost the photoconversion efficiency.…”
Section: Introductionmentioning
confidence: 94%
“…In this case, the destructive interference only occurs in a narrow wavelength range and this can be used to obtain spectrally selective light absorption. A recent study demonstrated the realization of efficient and ultrathin MOS cavities based on single crystalline Ge for spectrally selective photodetector applications . This strong light‐matter interaction for an MOS design is specifically important for 2D semiconductors, such as TMDs.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…This in turn induces an inherent limit in the performance of ultrathin amorphous based semiconductor designs. A recent study demonstrated a fabrication route for a sub‐10 nm single crystalline Ge layer for photodetection application . The authors claimed that this approach can also be adopted for other type of semiconductors.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…For this purpose, a series connection of cavities with doubleresonance behavior was utilized. Moreover, a recent study presents a fabrication route that synthe sizes nanometerscalethick, singlecrys talline Ge coatings for spectrally selective photodetection [67]. Incorporating an ultrathin Ge layer on top of a prede signed MI cavity leads to the formation of a spectrally selective metal-insula tor-semiconductor (MIS)based photo detector, as depicted in Figure 3(a)-(c).…”
Section: Photovoltaics and Photodetectionmentioning
confidence: 99%